Expression of Cox-2 in human breast cancer cells as a critical determinant of epithelial-to-mesenchymal transition and invasiveness. (February 2014) - Bocca, Claudia; Ievolella, Monica; Autelli, Riccardo; Motta, Manuela; Mosso, Luciano; Torchio, Bruno; Bozzo, Francesca; Cannito, Stefania; Paternostro, Claudia; Colombatto, Sebastiano; Parola, Maurizio; Miglietta, Antonella
<x xml:space="preserve">Abstract</x> Introduction: Cyclooxygenase-2 (COX-2) is overexpressed in several malignancies and is implicated in breast cancer progression. Objectives: We investigated whether changes in COX-2 expression may affect epithelial-to-mesenchymal transition (EMT) and then invasive potential of human breast cancer cells, in relationship with hypoxia. COX-2-null MCF-7 human breast cancer cells, MCF-7 cells transiently expressing COX-2 and COX-2-expressing MDA-MB-231 cells were employed. Results: COX-2 overexpression resulted in downregulation of E-cadherin and β-catenin, upregulation of vimentin, N-cadherin and SNAI1, suggesting EMT occurrence. COX-2-overexpressing MCF-7 cells were also characterized by increased invasiveness and release of matrix-metalloproteinase-9. The above-mentioned characteristics, homologous to those detected in highly invasive MDA-MB-231 cells, were reverted by treatment of COX-2-overexpressing MCF-7 cells with celecoxib, a COX-2-specific inhibitor, partly through the inhibition of COX-2-related intracellular generation of reactive oxygen species. Hypoxia further exacerbated COX-2 expression, EMT changes and invasive ability in both COX-2-overexpressing MCF-7 cells and MDA-MB-231 cells. Finally, immunohistochemistry performed on samples from normal and neoplastic human breast tissues revealed that COX-2-positive malignant cells were also positive for EMT-related antigens, hypoxia-inducible factor (HIF)-2α and the oxidative stress marker heme oxygenase. Conclusions: These findings support the existence of a direct link between COX-2 overexpression, EMT and invasiveness in human breast cancer cells, emphasizing the role of hypoxic microenvironment.